2008
DOI: 10.1002/adem.200700270
|View full text |Cite
|
Sign up to set email alerts
|

Freeze‐Casting of Porous Ceramics: A Review of Current Achievements and Issues

Abstract: Freeze‐casting, the templating of porous structures by the solidification of a solvent, have seen a great deal of efforts during the last few years. Of particular interest are the unique structure and properties exhibited by porous freeze‐casted ceramics, which opened new opportunities in the field of cellular ceramics. The objective of this review is to provide a first understanding of the process as of today, with particular attention being paid on the underlying principles of the structure formation mechani… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
859
0
13

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,055 publications
(948 citation statements)
references
References 76 publications
22
859
0
13
Order By: Relevance
“…We explored a versatile, readily accessible and inexpensive solutionphase materials shaping technique, namely freeze casting, to explore the possibility of assembling graphene sheets into corklike monoliths. Previous studies have demonstrated that when an aqueous suspension of nanoparticles is frozen, phase separation can result in the rejection of solid nanoparticles from the forming ice, which are then accumulated between the growing ice crystals 28,29 . If the fraction of nanoparticles is higher than the percolation threshold, the entrapped particles can form a continuous 3D network.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We explored a versatile, readily accessible and inexpensive solutionphase materials shaping technique, namely freeze casting, to explore the possibility of assembling graphene sheets into corklike monoliths. Previous studies have demonstrated that when an aqueous suspension of nanoparticles is frozen, phase separation can result in the rejection of solid nanoparticles from the forming ice, which are then accumulated between the growing ice crystals 28,29 . If the fraction of nanoparticles is higher than the percolation threshold, the entrapped particles can form a continuous 3D network.…”
Section: Resultsmentioning
confidence: 99%
“…Freeze casting has been successfully adopted to synthesize a variety of porous ceramic, metallic, polymeric and composite materials, including carbon nanotubes or graphene-based polymer composites 18,[30][31][32][33] . Although previous research on freeze casting has been centred on polymers and spherical particles 28,29 , we were particularly interested in studying how 2D graphene sheets interact with anisotropic ice crystal growth without the interference of other polymer or surfactant additives. In this work, GO, which can be readily produced from graphite in large quantities 2 , was chosen as a precursor to synthesize graphene-based monoliths.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides being as environmentally-friendly as freeze casting, it can be used to any material. For example, the shape and size of porous structure can be controlled precisely with ceramic materials, polymer materials, metal materials and composites [5], [6].…”
Section: Introductionmentioning
confidence: 99%